HUBUNGAN PENGAMBILAN KEPUTUSAN DENGAN KEBERHASILAN USAHA KEMITRAAN AYAM RAS PEDAGING DI KABUPATEN TABANAN - C. B. D. P., MAHARDIKA; SUPARTA, I N.; INGGRIATI, N. W. T. (Majalah Ilmiah Peternakan, 2018)
This research aims at determining the successful level of broiler contract farming and management decisionmaking ability. In addition, it was also conducted with the correlation of knowledge, attitude, motivation, perception and social interaction of farmers with the success of decision making and broiler contract farming. The research was carried out at Tabanan regency. There were 122 farmers as respondents using proportionate stratified random sampling and analyzed using by SEM-PLS. It showed that the successful level of broiler contract farming on middle level and most of farmers have abilities to make a good decision on broiler management. Knowledge, attitude and perception have positive significantly for decision making of broiler management, but motivation and social interaction had not significantly effected. Decision making gave positive effect to the success broiler contract farming.